Borderline personality disorder between emotional and relational instability and its relationship to some mental disorders - Fassi Benchalal, Amel (Journal of Human Sciences, 2022)
A borderline personality disorder is one of the most complex personality disorders due to its main characteristics, which is a pervasive pattern of instability in Emotional and interpersonal relationships, self-image, and affect, or through impulsive behaviors. All these features lead to the difficulty of differential diagnosis and show comorbidity Whether it is with personality disorders, Or through its relationships to some mental disorders, Such as depression or mood disorders, anxiety disorders or post-traumatic stressors, and even psychotic disorders.